Encapsulacion de semillas botanicas de algunas especies forstales - Carvajal O, C.=700 1 Peralta B, H.; Santtos B, R.; Hernandez T, M.
(En, Es)
Ilus., 11 ref.
Keywords: SEMILLAS; ARBOLES FORESTALES; ENCAPSULACION; CUBA